Synthesis and properties of 6-(2,6-dichlorophenyl)-3- (3-methyl-1H-pyrazol-5-yl)-6,7-dihydro-5H-[1,2,4]triazolo[3,4-b] [1,3,4]thiadiazine-7-carboxylic acid and its salts - S. O. Fedotov; A. S. Hotsulia (Zaporozhye State Medical University, 2023)
Carboxylic acids and their derivatives are an important component of many biological processes. For example, they can be used to create new medicines that can be useful in the fight against various diseases. Additionally, compounds containing a thiazole moiety may possess beneficial properties in practical pharmacy. The incorporation of this heterocyclic structure in molecules can positively impact several biological characteristics, such as anti-inflammatory, antiviral, and antifungal activities. Consequently, exploring novel compounds that combine a thiazole fragment with a carboxyl group holds promise for the advancement of new drugs and diagnostic tools that can contribute significantly to the battle against numerous diseases. The aim of the work was to create a number of organic and inorganic salts of 6-(2,6-dichlorophenyl)-3-(3-methyl-1H-pyrazol-5-yl)-6,7-dihydro-5H-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazine-7-carboxylic acid and study of their properties, as well as selective determination of the biological potential of these compounds. Materials and methods. The synthetic part of the study involved the sequential synthesis of the original compound 4-amino-5-(3-methyl-1H-pyrazol-5-yl)-1,2,4-triazole-3-thiol using a well-established method described in previous articles. The next stage involved the reaction of thiol with 2,3-dichlorobenzaldehyde in a medium of glacial acetic acid. The resulting Schiff base was subsequently reacted with 2-chloroethanoic acid in tetrahydrofuran in the presence of an equimolar amount of sodium hydride. Salts of the corresponding acid were formed during the reaction of 6-(2,6-dichlorophenyl)-3-(3-methyl-1H-pyrazol-5-yl)-6,7-dihydro-5H-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazine-7-carboxylic acid with both organic and inorganic bases in an aqueous-alcohol medium. The structures of all synthesized compounds were determined using 1H NMR spectroscopy and elemental analysis. Additionally, the individuality of each compound was confirmed using high-performance liquid chromatography-mass spectrometry. Results. The study determined the optimal conditions for the formation of both organic and inorganic salts of 6-(2,6-dichlorophenyl)-3-(3-methyl-1H-pyrazol-5-yl)-6,7-dihydro-5H-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazine-7-carboxylic acid. The analysis of pharmacokinetic parameters and physicochemical properties using ADME (absorption, distribution, metabolism, and excretion) allowed for the identification of promising synthesized compounds and the selection of more optimal compounds for further investigation. Conclusions. The structure of 12 compounds was synthesized and confirmed. Physical-chemical and pharmacokinetic analysis of ADME parameters was carried out and promising compounds were selected for more in-depth research.